Perbandingan Hasil Foundation Pada Rias Wajah Dengan Menggunakan Teknik Manual, Bakar, Dan Rendam Untuk Kulit Berminyak - Kamila, Safira Rahmah (Universitas Negeri Jakarta, 2024)
Abstract Application techniques foundation is a way of applying a product foundation on facial makeup. There are various application techniques foundation including manual techniques, burning, and soaking. The aim of this research was to determine the differences in facial make-up results using the three application techniques foundation the. The method used in the research is Pre-Experimental Design by using One Shot Case Study. Using sampling techniques purposive sampling with a research sample of 15 people. The data analysis technique uses descriptive percentage analysis and ANOVA. The analysis results show that there are differences between application techniques foundation in the sensory test, manual technique resistance indicators (64%), burn (89%), soak (56%), manual technique smoothness indicator (60%), burn (83%), soak (74%), manual technique evenness indicator (60%), grill (86%), soak (64%). In the preference test, the indicator is easy to stick with manual technique (68.33%), burn (92%), soak (62%), indicator is easy to flatten with manual technique (75%), burn (82%), soak (63%), indicator ease of application of manual techniques (72%), burn (83%), soak (62%), indicators of time efficiency for manual techniques (92%), burn (72%), soak (60%).